2012
DOI: 10.1021/bc200551b
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Methoxy Group in Immune Responses to mPEG-Protein Conjugates

Abstract: Anti-PEG antibodies have been reported to mediate the accelerated clearance of PEG-conjugated proteins and liposomes, all of which contain methoxyPEG (mPEG). The goal of this research was to assess the role of the methoxy group in the immune responses to mPEG conjugates and the potential advantages of replacing mPEG with hydroxyPEG (HO-PEG). Rabbits were immunized with mPEG, HO-PEG, or t-butoxyPEG (t-BuO-PEG) conjugates of human serum albumin, human interferon-α, or porcine uricase as adjuvant emulsions. Assay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
113
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 138 publications
(124 citation statements)
references
References 47 publications
(124 reference statements)
1
113
1
Order By: Relevance
“…59 In contrast to these findings, another recent study found that the methoxy group of PEG leads to immune responses; however, if replaced with a hydroxyl group, the immune response was not pronounced. 60 Moreover, nanoparticle size has a role in ABC regardless of PEG density and chain length. Nanoparticle sizes .…”
Section: Effect Of Different Peg Mw and Ph On Size And Zeta Potentialmentioning
confidence: 99%
“…59 In contrast to these findings, another recent study found that the methoxy group of PEG leads to immune responses; however, if replaced with a hydroxyl group, the immune response was not pronounced. 60 Moreover, nanoparticle size has a role in ABC regardless of PEG density and chain length. Nanoparticle sizes .…”
Section: Effect Of Different Peg Mw and Ph On Size And Zeta Potentialmentioning
confidence: 99%
“…Several studies have claimed that the PEG moiety of PEGylated therapeutic proteins itself might be immunogenic and could induce anti-PEG antibodies [27]. Further researches have indicated that the methoxy group within methoxy-PEG modified proteins played a critical role in the development of anti-PEG antibody with high affinity [27].…”
Section: Discussionmentioning
confidence: 99%
“…For this particular format, Casein in PBS from Thermo Fisher Scientific provided the lowest signal for the (14,15) previously reported on the detrimental effects of such surfactants on the sensitivity of detection for anti-PEG antibodies. Since our positive control antibody is PEG backbone unit specific, the interference was expected.…”
Section: Assay Buffermentioning
confidence: 99%